2016
DOI: 10.4077/cjp.2016.baf441
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Semen Quality in Men in Northern Taiwan between 2001 and 2010

Abstract: Semen quality is a key indicator of the male reproductive ability. The decline in semen quality has been debated for several decades. However, data on decline in semen quality might be inconsistent given factors such as geographical area, ethnicity, environmental exposure and lifestyle changes. This study aimed to provide information on the semen quality of men in Northern Taiwanese. We recruited 7,187 male participants between 2001 and 2010 from a reproductive medical center. The age of the participants range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Recently, a rigorous and comprehensive metaanalysis of studies conducted between 1973 and 2011 reported that among men from western countries, sperm counts (measured either by sperm concentration or total sperm number) have declined by more than 50% (Levine et al, 2017). Likewise, a variety of other studies have also reported that semen quality is continuously declining (Li et al, 2016;Sengupta et al, 2017;2018). Although previous studies have demonstrated that some risk factors, including herbicides, pesticides and environmental pollutants, might be associated with decreased semen quality, the underlying causes of decreasing semen quality are largely uncertain (Xiao et al, 2001;Sharpe, 2010;Bloom et al, 2015;Chiu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a rigorous and comprehensive metaanalysis of studies conducted between 1973 and 2011 reported that among men from western countries, sperm counts (measured either by sperm concentration or total sperm number) have declined by more than 50% (Levine et al, 2017). Likewise, a variety of other studies have also reported that semen quality is continuously declining (Li et al, 2016;Sengupta et al, 2017;2018). Although previous studies have demonstrated that some risk factors, including herbicides, pesticides and environmental pollutants, might be associated with decreased semen quality, the underlying causes of decreasing semen quality are largely uncertain (Xiao et al, 2001;Sharpe, 2010;Bloom et al, 2015;Chiu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…How to curb the decline in semen quality and improve regional reproductive health is an urgent and important issue in many countries and regions. 4 17 The main symptoms of male infertility can be divided into azoospermia, low semen volume, asthenozoospermia, and teratozoospermia. Studying the main types, composition, and trends of abnormal semen symptoms in male infertile populations is important for guiding the prevention and treatment of regional male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this is the first study on time trends in semen quality among Chinese men in Henan Province. Studies [2][3][4][5][6][7][8][23][24][25] suggest that semen quality is declining globally, however, the debate remains open due to the possible effects of ethnic and geographical differences. In contrast, several other studies have reported no significant change in semen quality [9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…The annualized rate of decline in the total motility was lower than that reported in America (2% per year) 23 , but it was higher than that reported in Paris (0.6% per year) 2 and Marseille (0.4% per year) 4 . The possible reasons for the discrepancy are as follows: (1) small sample size are used in the previous study 10,11 ; (2) subjects in these studies are fertile men 2,3,11 or infertile men 5,21,25 ; (3) there are differences in lifestyle habits, ethnicity, and geographical regions [2][3][4][5][6][7][8][9][10][11][22][23][24][25] ; (4) the different study periods [2][3][4][5][6][7][8][9][10][11][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%